Pengaruh Sistem Kartel terhadap Stabilitas Persaingan Usaha di Indonesia - I Putu Ari Santika Putra; Ni Luh Made Mahendra Wati; I Nyoman Sutama (Jurnal Preferensi Hukum, 2020)
A cartel is an agreement made by a business actor with its competitors to gain excessive profits, which is stated in article 11 of Law No. 5 of 1999 concerning anti-monopoly and unfair business competition in Indonesia, the influence of cartels in business competition can cause unfair competition, damage market stability, and shut down competition in a particular market. The objectives presented in this study are to determine the forms of cartels that usually occur in limiting unfair business competition in Indonesia, and to determine the factors used by KPPU in identifying early indicators of cartel systems. This study uses a normative legal method with rationality which examines the influence of the cartel system on the stability of business competition in Indonesia, which appears to have experienced norm blur. The data source used in solving problems is the statutory approach. Literatures, journals and various related documents. The results of the discussion show that cartels have several types, namely regional cartels, production, prices, conditions, profit sharing, the influence of the cartel system in business competition which has a negative impact which causes unfair business competition, as well as harms various parties ranging from business actors, consumers, to the government. Then, in identifying the occurrence of cartels, there are several factors used by KPPU, namely structural factors consisting of the level of market concentration, number of companies, company size, homogeneity of goods or services, multi-market contacts, supply and production capacity, ownership linkages, ease of entry. specific market share, the character of demand. The next factor is the behavioral factor which is divided into two parts, starting from transparency and information exchange.